Analisis Citra Perempuan dalam Novel Cantik Itu Luka Karya Eka Kurniawan Kajian Kritik Sastra Feminisme Marxis - Padmasari, Lintang Omega; Nugraha, Setya Tri (JP-BSI (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
This study analyzes the image of women in the novel Cantik Itu Luka by Eka Kurniawan. The aims of this study were: (1) to identify and describe the self-image of women in the novel Cantik Itu Luka by Eka Kurniawan, (2) to identify and describe the social image of women in the novel Cantik Itu Luka by Eka Kurniawan. The theory used in this study is literary criticism of Marxist feminism. This study uses descriptive qualitative research with data on a novel entitled Beauty Is a Wound. The data in this study are in the form of words, phrases, sentences, or paragraphs which contain self-image and social image of women in the novel Cantik Itu Luka. The data collection technique used is the technique of reading and noting. Qualitative descriptive data analysis was carried out in three stages, namely; (1) Data reduction; (2) Data Presentation, (3) Drawing Conclusions. The results of the study found the image of women in the novel Cantik Itu Luka. This study found four forms of female image, namely (1) physical aspect of self-image, (2) psychological aspect of self-image, (3) social image of family aspect, (4) social image of community aspect. Each sub-problem has causes for the image of women, such as: physical assessment of female characters, psychological assessments, family assessments of female figures, and community assessments of female figures. The implications of this research can be used for the general public and language learning, namely reviewing the contents of the novel.